2017
DOI: 10.1002/eji.201646819
|View full text |Cite
|
Sign up to set email alerts
|

NK cells generate memory‐type responses to human cytomegalovirus‐infected fibroblasts

Abstract: Natural killer (NK) cells are cytotoxic lymphocytes that selectively respond against abnormal cells. Human cytomegalovirus (HCMV) infection causes expansion of NKG2C CD57 NK cells in vivo and NKG2C NK cells proliferate when cultured with HCMV-infected cells. This raises the possibility of an NK-cell subset selectively responding against a specific pathogen and accruing memory. To test this possibility, we compared proliferation, natural cytotoxicity and interferon-γ (IFN-γ) production of NK cells from HCMV-ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The relevance of HLA-E-NKG2C interactions for the expansion of adaptive NK cells has been demonstrated in vitro ( 2 , 74 , 75 , 76 ) and is supported by studies showing that NKG2C zygosity directly correlates with NKG2C surface levels and the size and distribution of NKG2C + NK cells in vivo ( 77 79 ).…”
Section: Hcmv-driven Priming and Expansion Of Adaptive Nk Cellsmentioning
confidence: 79%
“…The relevance of HLA-E-NKG2C interactions for the expansion of adaptive NK cells has been demonstrated in vitro ( 2 , 74 , 75 , 76 ) and is supported by studies showing that NKG2C zygosity directly correlates with NKG2C surface levels and the size and distribution of NKG2C + NK cells in vivo ( 77 79 ).…”
Section: Hcmv-driven Priming and Expansion Of Adaptive Nk Cellsmentioning
confidence: 79%
“…CD57 hi NKG2A − NKG2C − expanded populations have been observed in both NKG2C sufficient and deficient subjects; a recent study identified expansion of FcRγ – LIR‐1 + cells in both NKG2C + and NKG2C − NK cell populations among CMV + renal transplant patients, irrespective of their KLRC2 genotype, although the FcRγ – LIR‐1 + NKG2C − cells displayed greater ADCC against anti‐CMV antibody‐coated targets than did the FcRγ – LIR‐1 + NKG2C + population . A recent report analyzing expansion of NK cells against HCMV‐infected targets in vitro demonstrated expansion of NK cells independently of NKG2C expression . It is not yet clear what drives the expansion of these CD94/NKG2C‐ NK cells.…”
Section: Hcmv Infection Leads To Accumulation Of Terminally Differentmentioning
confidence: 99%
“…Likewise, CMV infection drives the selective expansion of NKG2C + NK cells in rhesus macaques (Ram et al, 2018). Co-culture of human peripheral blood lymphocytes with HCMV-infected fibroblasts in vitro has been reported to drive the selective expansion of NKG2C + NK cells in some (Guma et al, 2006), although not all studies (Newhook et al, 2017).…”
Section: Cytomegalovirus (Cmv)mentioning
confidence: 99%